2016
DOI: 10.1021/acs.jproteome.6b00266
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gas-Phase Oxidation and Localization of Alkylated Cysteine Residues in Polypeptide Ions via Ion/Ion Chemistry

Abstract: The thiol group in cysteine residues is susceptible to several post-translational modifications (PTMs), including prenylation, nitrosylation, palmitoylation, and the formation of disulfide bonds. Additionally, cysteine residues involved in disulfide bonds are commonly reduced and alkylated prior to mass spectrometric analysis. Several of these cysteine modifications, specifically S-alkyl modifications, are susceptible to gas-phase oxidation via selective ion/ion reactions with periodate anions. Multiply proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…Activation of the [M+H+O] + species generated in the gas-phase was compared to the [M+H+O] + species generated via solution-phase oxidation and the resulting spectra were identical suggesting that these two species were of the same primary structure. It was then found that the gas-phase ion/ion oxidation of thioethers was a general phenomenon as S-alkyl cysteine residues were also shown to undergo this oxygen transfer chemistry [53]. This was demonstrated with S-ethyl, S-farnesyl, and S-carbamidomethyl cysteine residues upon ion/ion reactions between doubly protonated peptides and both periodate and peroxymonosulfate anions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the [M+H+O] + species generated in the gas-phase was compared to the [M+H+O] + species generated via solution-phase oxidation and the resulting spectra were identical suggesting that these two species were of the same primary structure. It was then found that the gas-phase ion/ion oxidation of thioethers was a general phenomenon as S-alkyl cysteine residues were also shown to undergo this oxygen transfer chemistry [53]. This was demonstrated with S-ethyl, S-farnesyl, and S-carbamidomethyl cysteine residues upon ion/ion reactions between doubly protonated peptides and both periodate and peroxymonosulfate anions.…”
Section: Resultsmentioning
confidence: 99%
“…For methionine residues this results in a loss of 64 Da corresponding to the ejection of methanesulfenic acid, a pathway that is well documented by groups investigating the solution-phase oxidation of methionine residues [3741]. Interestingly, the loss of alkyl sulfenic acids from oxidized S-alkyl cysteine residues results in the generation of a dehydroalanine residue (Dha) at the site of the original modified residue [53,54,55,56]. This is especially useful as Dha residues open a low energy pathway that leads to cleavage of the N-C α bond of the Dha residue to generate c- and z-ions upon CID [56,57,58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated previously, peptides containing easily oxidized moieties (i.e., methionine residues [25], S-alkylated cysteine residues [24], and disulfide bonds [23]) yield dominant [M+H+O] + species due to oxygen transfer from the reagent anion to the reactive side-chain upon activation of peptide/periodate ion/ion complexes. Here, we show that peptides lacking easily oxidized residues can also undergo oxidation upon ion/ion reaction with IO 4 − .…”
Section: Resultsmentioning
confidence: 99%
“…The gas-phase oxidation of disulfide bonds [23], S-alkyl cysteine residues [24], and methionine and tryptophan residues [25] via ion/ion reactions with periodate anion has recently been demonstrated. Furthermore, the oxidation of protonated polypeptides to [M+H+O] + , [M-H] + , and M +• species upon ion/ion reactions with a suite of reagents derived from persulfate has been demonstrated [26].…”
Section: Introductionmentioning
confidence: 99%